When the Soviets came to stay: Soviet influence on Cuban cultural institutions, 1961-1987 - Story, Isabel (2017)
Cuba’s post-1960 political and economic relationship with the USSR has long been debated, especially the extent to which the connection shaped the Cuban Revolution. Consequently, readings of the occasionally conflictive relationship between Cuba’s state authorities and its cultural world have often relied on stereotypes inherited from Western interpretations of the USSR or the 1948-89 Socialist Bloc; such readings assuming that cultural policy was clearly defined and enforced by Soviet-style apparatchiks or Castro. While perhaps understandable for 1971-6, when the National Cultural Council (CNC) was led by ex-members of the pre-1959 communist party, recent research suggests that we look beyond the surface to see that ‘policy’ was often empirically formed and constantly challenged. Yet, perhaps due to those common assumptions, little has been written about real Soviet influence on Cuban culture, and different sub-periods during the 30-year Cuban-Soviet alliance have largely been ignored.